Commentary on the Synthesis and Structures of Unsupported Cycloarsoxane Compounds. Issue 2 (4th March 2018) - Bani-Fwaz, Mutasem Z.; Fazary, Ahmed E.
Abstract : This comment describes the available synthetic routes and some general structural features of unsupported cycloarsoxane compounds. The key synthetic strategies used to prepare this type of compound and the significant roles that they have been employed in after coordination to the metal center are fully discussed. The literature herein covers all known unsupported cycloarsoxane compounds that have been structurally characterized by X-ray diffraction techniques.